Improved Intra-coding Methods for H.264/AVC. (19th February 2009) - Song, Li; Xu, Yi; Xiong, Cong; Traversoni, Leonardo
Abstract : The H.264/AVC design adopts a multidirectional spatial prediction model to reduce spatial redundancy, where neighboring pixels are used as a prediction for the samples in a data block to be encoded. In this paper, a recursive prediction scheme and an enhanced (block-matching algorithm BMA) prediction scheme are designed and integrated into the state-of-the-art H.264/AVC framework to provide a new intra coding model. Extensive experiments demonstrate that the coding efficiency can be on average increased by 0.27 dB with comparison to the performance of the conventional H.264 coding model.